Effect of Informed Consent on Patient’s Anxiety Regarding Third Molar Surgery (Medical Forum Monthly, 2024)
Objective: To assess mean change in anxiety of a patient undergoing 3rd molar surgery before and after disclosureof information regarding procedure.Study Design: A descriptive studyPlace and Duration of Study: This study was conducted on 50 patients that were presented to the outpatientdepartment of a tertiary care hospital in FUCD between December 2018 to November 2019.Methods: Patients reporting to OMFS department of FUCD for surgical removal of impacted 3rd molars wereselected after history, clinical examination & radiographic evaluation. Informed consent form was given to thepatients starting by explaining the brief overview of procedure, benefits and racial complications. Patients wereasked to sign the informed consent form. Anxiety of patient after taking informed consent is evaluated by STAIform. The level of anxiety by using STAI on first visit and later again using the STAI on the day of procedure wascompared.Results: A total of 50 patients where 13(26.0) males and 37 (74.0) female patients having mean age (years)29.00±6.96 were included in the study. Our study finding showed that mean change in anxiety of patient undergoing3rd molar surgery and after disclosure of information regarding procedure was 35.06±2.25 and 45.60±2.50respectively with mean change 10.53±0.25.Conclusion: The study concluded that patient experienced anxiety when underwent molar surgery. So there is aneed of patient counseling about the procedural risks and associated complications regarding 3rd molar surgery in asequential manner